Improving the Properties of Oil Palm Shell (OPS) Concrete Using Polyvinyl Alcohol (PVA) Coated Aggregates - Johan, M.R; Singho, N.D (Trans Tech Publications, Switzerland, 2014)
Recycling and reusing waste materials as aggregate replacement play an important role in solving issues associated with environmental problems and depletion of non-renewable resources. The use of these waste materials as aggregate is highly desirable as it can serve to sanitise the environment and create cheaper, renewable aggregates which will provide a double advantage as cost effective construction material and waste disposal at the same time. Hence, there is growing interest in this research area to promote safe and economical use of waste material as aggregate alternative in concrete. In Malaysia, where oil palm shell (OPS) is generated in abundance from the oil palm industry, reusing OPS as concrete aggregate replacement has been widely studied. Results from previous studies have shown that OPS concrete can be used in practical application as structural lightweight concrete. However, the properties of OPS can be further improved to achieve better performance of the resulting concrete. Polyvinyl alcohol (PVA) is a water-soluble synthetic polymer which is extensively used in all kinds of industries, such as papermaking, adhesive for plywood, printing and even in the construction industry as internal wall coating, plasterwork and joint sealing. It has been found that PVA has the potential to improve the quality of the OPS aggregates and hence enhance the resulting concrete properties. In this paper, an experimental program on concrete produced from PVA coated OPS aggregates is presented. The PVA treated OPS concrete was tested for slump, air-dry density, compressive strength, and water absorption. It was found that PVA treated OPS concrete had significant improvement in its compressive strength as compared to raw OPS concrete. It was determined that PVA treated OPS concrete can achieve 28-day compressive strength of up to 33.53 MPa. Moreover, it was also determined that there was a decrease of 0.67% in the water absorption of PVA treated OPS concrete as compared to the raw OPS concrete. In general, the investigation results showed that PVA can be used to improve the OPS concrete properties for the production of structural lightweight concrete.